Validation of Perceived Ability in Statistical concepts Questionnaire (PASQ) Based on Rasch Measurement Model - Ismail, Nor-Zatul Iffa; Mahmud, Zamalia; Abu Kassim , Noor Lide; Said, Zainol (IEEE, 2012)
This paper describes the process of assessing the unidimensionality and validity of the Perceived Ability in Statistical Concepts Questionnaire (PASQ) based on the Rasch Measurement Model. Students’ perceived ability was measured by a self-developed 30 PASQ items of Likert-scale format comprises of concepts on types of data (6 items), graphical representations of distributions (8 items), measures of central tendency (8 items), and measures of variability (8 items). The process of assessing the validity of PASQ involved a collection of data from 416 students at four institutions of higher learning in Malaysia where the measurement of construct validity for the overall PASQ and its subscales were established using Winsteps 3.68.2. Various Rasch measurement tools were utilized to demonstrate the true unidimensionality and validity measure of the PASQ and in meeting the needs of the Rasch measurement model. The findings show that the validity and unidimensionality of PASQ can be truly established and can satisfy the characteristics of the Rasch measurement model.